Two Narratives about Kosovo’s Political Friends: A Critical Discourse Analysis of Articles in Two Newspapers - Muzbeg, Esin; Tahiri, Lindita (Information & Media, 2022)
This article analyzes the portrayal of the USA and NATO as Kosovo’s friends in the Kosovan media discourse. The research will use the Critical Discourse Analysis based on the model by Van Dijk to demonstrate the production and continuity of the friendship discourse in the Kosovan media. Two daily media outlets are analyzed: Koha Ditore and Epoka e Re, focusing on the strategies used to construct the image of Kosovo’s friends for the countries that have supported the independence of the new state of Kosovo. The ideological framing of the friendship discourse is pointed out as the dominant topic in these two mainstream newspapers, but on the other hand, the papers emphasize two different perspectives of using the discourse of friendship, which are adjusted to the editorial policies and persuasive goals of the respective papers.